Perceived Stress as a Mediator in the Relationship between Time Perspectives and Alcohol Consumption - Nashria, Sry Ayu; Indirasari, Dyah Triarini (Psychological Research on Urban Society, 2021)
Heavy drinking is injurious to health and may even lead to death. Previous studies showed that Past -Negative, Present-Fatalistic, and Future time perspectives influence alcohol consumption; however, this study presents evidence that contradicts these claims. Lazarus and Folkman’s (1984) transactional model of stress and coping explains that cognitive processes, such as perceived stress, are responsible for individual choices of coping strategies or decision to consume alcoholic beverages. Personal factors also influence time perspectives. This study applies the aforementioned model to hypothesize that the relationship between time perspectives and alcohol consumption is mediated by perceived stress. A total of 307 participants aged 18–22 years (late adolescence) who were habitual consumers of alcohol participated in this study. Mediation analysis was employed and it was revealed that perceived stress did not mediate the relationship between Past-Negative and Present-Fatalistic time perspectives and alcohol consumption. However, perceived stress was found to be a mediator in the relationship between Future time perspective and alcohol consumption. To summarize, dominant Past-Negative and Present-Fatalistic time perspectives can cause alcohol consumption in individuals who possess specific characteristics. Conversely, stress can precipitate alcohol consumption for individuals evincing the Future time perspective.